Chemical constituents and biological activities of the leaves of Garcinia griffithii(Guttiferae) - Nik Sazali, Nik Shazwani Afifah; Ahmad, Farediah; Bakhtiar, M. Taher (2011)
Chemical investigation of the leaves of Garcinia griffithii(Guttiferae) has been carried out. The crude extract was obtained by using soxhlet extraction with n-hexane (n-Hexane) and methanol (MeOH) as the solvents. The MeOH crude exhact of the leaves of G. grifftthiiwere screened for antioxidant activity by DPPH method. The result suggested that the extract was potentialantioxidant agent. The crude MeOH extract of G. griffithiiwas found to show free radicalscavenging activity with (lCso = 2995.11 pg/ml). The results of totalphenolic content assays indicated that methanolic crude extract ior G. griffithii contained phenolic compounds. The total phenolic contents ol G. griffithii was expressed as pg gallic acid equivalent (GAE/L)(406.31 s 2.39 pg/ml)and pg (i)-cathechin equivalent (CEiL)(BB1.Bg r 5.56 pg/ml). The n-hexane extract was purified by using vacuum liquid chromatography (VLC) and column chromatography (CC) to get pure compounds. The structures were elucidated by spectroscopic techniques such as lR and NMR (1H, 13C and DEPT) spectroscopy and GC-MS. lsolation and characterization of the n-Hexane crude extract of G. oriffithiihave afforded soualene. friedooleanan-3-one and stigmasta-5-en-3-ol.